Distribution functions of adsorption sites on the surface of stainless steel during water vapor adsorption. (January 2018) - Rozanov, Leonid Nicolaevich
Abstract: Adsorption methods for determining the properties of stainless steel surface are presented. The relation between the actual and geometric surface is determined. The dependence of adsorption heat on the coverage logarithm is derived from experimental adsorption isotherms for water at 298 K. On the basis of this dependence, differential and integral distribution functions of adsorption sites by adsorption heat is calculated. It is shown that in the case of water adsorption on the surface of stainless steel at 298 K, adsorption heat for 90% of adsorption sites ranges from 4.4 × 10 7 to 7.9 × 10 7  J/kmol. Highlights: Henry and Freundlih equations has permitted to derive the dependence of the heat of adsorption on the adsorbed gas amount. The energetic distribution functions of adsorption sites are calculated analytically from the Freundlich isotherm equation. Pump-down curve is used to find Freundlich isotherm coefficients. And it was shown that adsorption heat for 90% of adsorption sites ranges from 4.4 × 10 7 to 7.9 × 10 7  J/kmol.